PENINGKATAN KEMAMPUAN LITERASI NUMERASI SISWA MELALUI PEMBELAJARAN MATEMATIKA TERINTEGRASI BERBASIS PROYEK PADA MATERI GEOMETRI - Nur Ainun; Cut Nurul Fahmi; Mukhtasar Mukhtasar; Khairul Asri (Jurnal Dedikasi Pendidikan, 2024)
Numerical literacy is the ability students need to understand the world and equip students to understand and analyze information as well as the use of mathematical reasoning to solve problems in everyday life. However, several previous studies stated that students' literacy skills in Indonesia are still low. This research was conducted aiming to determine the increase in students' numeracy literacy skills through project-based integrated mathematics learning on geometry material. This research is experimental research with pretest-posttest control group design. The population in this research were all class VII students of SMP Negeri 1 Darul Imarah Aceh Besar, which consisted of five classes. Meanwhile, the sample consisted of two classes, namely the experimental class and the control class which were taken by random sampling. Data on numeracy literacy skills were obtained from a written test in the form of multiple-choice questions. With the acquisition of a significance value of 0.039 <0.05, it indicates that the result of increasing students' numeracy literacy skills taught by project-based mathematical learning model of geometry material better than the controlled class which was taught by conventional learning models.